Cloud Computing based Learning Management System (CC-LMS) implementation model in Malaysia Higher Education Institutions - Kassim, Rahimah (2021)
In the education arena, cloud computing is more apparent in technology to ensure the availability and sharing of resources through virtualization. Despite its attractiveness and benefits, the Higher Education Institution (HEIs) are still hesitant to implement cloud computing services due to insufficient details on issues and priorities in implementing cloud computing services. Therefore, this study aims to explore the potential benefits and obstacles of cloud computing in Learning Management System (LMS) and determine the key success factors of cloud computing implementation for LMS (CC-LMS) operations in HEIs. By synthesizing literature from various industries, this study proposes a conceptual model of Critical Success Factors (CSFs) based cloud computing implementation for HEIs. This framework was extracted from the various aspects of the industry and integrated into the Technological, Organizational, and Environmental (TOE) framework. The research methodology consists of rigorous data collection and quantitative and qualitative data analysis that allows for more substantive conclusions to enable viable CC-LMS operation. The Delphi technique was adapted to assist in the data collection and judgment process. The two-round Delphi survey has been conducted with 18 (1st round) and 13 (2nd round) cloud computing technology and LMS experts from local HEIs and service vendors to assist in the judgment process. This analysis resulted in a consensus after the second round of Delphi survey with the suggestions on the high importance of several factors in implementing a cloud computing system for LMS in HEIs. As a result, on the benefit of this technology, most participants agreed that this technology enhances the technology infrastructure and maintenance, which is synchronized with the main obstacle of CC-LMS implementation, poor infrastructure performance. Finally, the study is expected to provide HEIs decision-makers with a better understanding and guidelines of cloud computing implementation characteristics with the relevant perception of current services.